Some negative contents portrayed in English song lyrics - Liliek Soepriatmadji; Katharina Rustipa (Universitas Islam Sultan Agung, 2020)
Some song lyrics may have been banned or rescheduled for their radio and television broadcasts. Those song lyrics were claimed to propagandize negative contents. Recently West Java Broadcasting Commission has regulated the broadcast of 17 western songs for the prejudice of negative contents. Based on semantic analysis of those song lyrics, the authors finally found out that they qualitatively describe lust, profanity, drug and alcohol abuse, etc. through periphrasis, simile, litotes, meiosis, and other speech figures. Clauses were selected to deliver the figures of speech of the lyrics sung by mostly male singers and the male-female duets in pop and r and b music genres.